PECULIARITIES OF FINANCIAL MONITORING IN UKRAINE UNDER MARTIAL LAW - Rubai О.; Sholudko О.; Bohach М. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article is devoted to studying the peculiarities of financial monitoring in Ukraine under the conditions of martial law, factors affecting the financial and economic security of the country. The research outlines the problems of formation of the financial monitoring system caused by the high degree of economy shadowing, corruption, underdevelopment of the financial market, duplication of powers by various bodies and departments, low automation and information exchange. The dynamics of informing financial transactions by banking institutions is considered. The authors of the work analyze new rules of financial monitoring for the period of martial law. They are related to the financial transactions that do not require naming the sources of funds during the period of martial law; a simplified procedure for identification and verification of buyers of military bonds; stop of the scheduled and unscheduled on-site inspections. The paper gives characteristics of the financial monitoring by banks when their individual customers deposit cash into their current accounts, namely when the individual bank customer deposits cash into the current account in an amount that corresponds to or exceeds the threshold of the financial transaction and the restoration of expenditure transactions with them during the period of martial law without establishing the source of their origin. The article describes the procedure of the bank’s actions in case of suspicious financial transactions and the procedure for freezing assets deposited by the client, who is a natural person, in cash, when the assets are related to the funding of terrorism and financing of the proliferation of weapons of mass destruction. The bank is obliged to freeze these assets immediately, without prior notification of the client, a natural person., and notify the Security Service of Ukraine in accordance with the procedure established by the law about such frozen assets.